The EU's future prosperity: What role for the fiscal framework? - Iain Begg; Daniel Cicak (EconPol Forum, 2024)
Public investment has been low in recent years, resulting in shortcomings in infrastructure and other public assets capable of underpinning economic growth and competitiveness. Efforts at the EU level to establish a Sovereignty Fund intended to enhance competitiveness and to respond to the likes of the US Inflation Reduction Act have been watered down, as have plans to boost funding for the Strategic Technologies for Europe Platform. Although golden rules have fallen out of favor in some jurisdictions, there is a case for a fresh look at how such rules, applied at both the EU and member state levels, could boost the quality of public finances and competitiveness. Three principles for a revived approach to golden rules could be: a focused, but more open approach to eligible spending, as opposed to conventional national accounting definitions of investment; scrutiny of government plans by independent financial institutions or similar; and the adoption of a medium-term perspective. Building on the analytic reviews by Mario Draghi on competitiveness and Enrico Letta on the single market, funding EU public goods by issuing debt should be furthered, rather than relying on the constrained resources of the EU budget.
Keywords: 330